A rare case of ascending colon adenocarcinoma incarcerated in an inguinoscrotal hernia: case report and literature review - Tien Yew Chern; Yeng Kwang Tay; Dayashan Shevantha Perera (Surgical Case Reports)
Abstract Background Inguinal hernias and colorectal cancers are common conditions, but the presentation of a loop of bowel containing cancer within a hernia is rare. Principles of surgery include oncological resection of the involved colonic segment as well as lymphatic drainage. Based on case reports of the last several decades, there have been no reports of a case where the reduction of an inguinoscrotal hernia and oncological colectomy were performed completely laparoscopically. We present the first instance of a completely laparoscopically assisted resection and hernia repair on a patient with T4 ascending colon cancer. A literature search on recent case reports over the last 30 years has also been presented with a focus on trends in treatment. Case presentation An 83-year-old man presented for further investigation of his iron deficiency anaemia and was diagnosed with adenocarcinoma of the ascending colon. This was demonstrated radiologically to be found within a large right inguinoscrotal hernia. He underwent a laparoscopically assisted right hemicolectomy and laparoscopic closure of the internal ring and recovered well. Conclusions Colorectal cancers within inguinal hernias are rare and can often present with complications such as perforation. As such, treatment has mostly involved an open operation. The last few years have shown feasibility of a laparoscopic approach and can be attempted safely when indicated.